THE ART OF DIPLOMATIC COUNSELING: COUNSELING VALUES IN THE STORY OF PROPHET SULAIMAN AND QUEEN BALQIS - Muarif, Ahmad Syamsul; wadi, Hamzan (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
This study aims to examine, identify and analyze the counseling values ??contained in the story of Prophet Solomon and Queen Balqis, by highlighting the diplomatic approach used as the art of counseling in resolving conflicts and building harmonious relationships. Through a qualitative method with a document study type to examine the counseling values ??in the story of Solomon and Balqis. Data collection was carried out through documentation and observation studies, as well as data triangulation to ensure the validity of the findings. Data analysis used the Miles and Huberman model which includes three stages: data reduction, data presentation, and drawing conclusions. This study found that Prophet Solomon applied the principles of diplomatic counseling in the form of open dialogue, peaceful negotiation, and respect for other parties before making strategic decisions. The story of the interaction between Prophet Solomon and Queen Balqis, which began with the sending of a letter of invitation to dialogue and was responded to with an exchange of gifts and a diplomatic visit, reflects the art of counseling based on wisdom, empathy, and inclusiveness in building effective communication. The main values ??identified include: deliberation, empathy, conflict resolution, and wisdom. This study concludes that the story of Prophet Solomon and Queen Balqis can be a role model in implementing relevant counseling guidance to be applied in counseling practices in the modern era, especially in the context of conflict resolution and leadership strengthening.